Implementasi Sistem Merit pada Aparatur Sipil Negara di Indonesia: The Implementation of Merit-Based System on State Civil Apparatus in Indonesia - Anggita Chairiah; Ariski S; Agus Nugroho; Adi Suhariyanto (Jurnal Borneo Administrator, 2020)
High performance and competency are the demands that nowadays must be owned by State Civil Apparatus known as ASN. Those demands can be achieved if the human resources' screening process is carried out lawfully and correctly by procedures. This article aims to examine the management of State Civil Apparatus in Indonesia using the merit system theory based on several phenomena. The data were analyzed using qualitative techniques, namely a descriptive phenomenological analysis. The discussion focuses on the development and particular phenomenon of the merit system in Indonesia's current situation, starting from the beginning of the selection and recruitment process, the placement of ASN, and implementing a merit system based on competency. Research result showed that the implementation of the merit system in Indonesia has not yet been thoroughly carried out based on the right procedures. More importantly, to become a dynamic governance also requires firm awareness of all stakeholders' responsibility, which is the primary key to executing a merit system in Indonesia. However, the improvement of supervision also needs to be done, especially by KASN, to optimize the merit system's implementation. Keywords: Merit System, State Civil Apparatus (ASN), Performance Appraisal, Human Resource Management Abstrak Kinerja dan kompetensi tinggi merupakan salah satu tuntutan yang harus dimiliki ASN saat ini. Hal ini bisa diwujudkan jika proses penyaringan sumber daya manusia yang unggul dilakukan dengan jujur dan benar sesuai dengan prosedur. Artikel ini bertujuan untuk mengkaji manajemen Aparatur Sipil Negara di Indonesia menggunakan teori sistem merit berdasarkan beberapa fenomena yang ada. Data dianalisis menggunakan teknik analisis data kualitatif, yakni descriptive phenomenological analysis. Pada pembahasan fokus penelitian, dipaparkan pelaksanaan serta beberapa fenomena penerapan sistem merit pada ASN di Indonesia saat ini dari awal proses seleksi dan rekrutmen, penempatan ASN hingga penerapan sistem merit berdasarkan kompetensi. Hasil penelitian menemukan bahwa penerapan sistem merit di Indonesia masih belum sepenuhnya dilakukan sesuai prosedur. Kunci sukses lainnya, agar menjadi dynamic governance diperlukan kesadaran penuh dari semua pemangku kepentingan dalam menerapkan sistem merit di Indonesia. Namun, peningkatan pengawasan juga perlu dilakukan terutama oleh KASN agar implementasi sistem merit dapat optimal. Kata Kunci: Sistem Merit, Aparatur Sipil Negara (ASN), Penilaian Kinerja, Manajemen Sumber Daya Manusia